Improving Student Learning Outcomes on Cell Structure and Function Material Using Case Method Learning for Class X at MA- Arrohmah Ledokombo - Baidawi, Moh. Jian Sukron (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
This study aims to enhance the learning outcomes of Grade X students at MA Ar Rohmah through the implementation of Classroom Action Research (CAR). The participants consisted of 25 students from Grade X. The study employed a two-cycle CAR design, with each cycle comprising the stages of planning, implementation, pretest, post-test, and reflection. Data were collected through learning outcome tests and student activity observation sheets. The findings demonstrate a consistent improvement in students’ learning outcomes following the implementation of the classroom actions. In the first cycle, the average student score increased compared to the pre-action results; however, not all students met the Minimum Passing Grade (KKM). In the second cycle, after several instructional improvements were made, the average student score rose significantly, and the majority of students achieved or surpassed the established KKM. These results suggest that the systematic implementation of appropriate classroom action strategies can effectively improve the learning outcomes of Grade X students at MA Ar Rohmah.